ANALISIS ANTRIAN PASIEN INSTALASI RAWAT JALAN RSUP Dr. KARIADI BAGIAN POLIKLINIK, LABORATORIUM, DAN APOTEK - Rany Wahyuningtias; Dwi Ispriyanti; Sugito Sugito (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2013)
Queue process is a process of the coming of a customer to a service facility, then waiting in line (queue) when the officers busy, and leaving the place after getting the service. Patient’s line at RSUP DR. Kariadi is a lot enough then it will making the service from the hospital isn’t optimal as a result. Hence, it needed a queue model to optimize the service to patient. From the result of the analysis in RSUP Dr. Kariadi it gives the best queue models is in polyclinic area second floor, laboratory, and pharmacy.